The Influence of Natural and Surgical Menopause on Cardiovascular Risk Markers Folate and Vitamin B12 Levels - Hakan Kıran; Deniz Cemgil Arıkan; Gürkan Kıran; Ayhan Coşkun; Semih Yancar; Abdullah Tok; Hasan Çetin Ekerbiçer (Medical Network, 2011)
OBJECTIVE: To investigate the influence of both natural and surgical menopause on serum concentrations of lipids, lipoprotein-a, C-reactive protein, homocysteine, folate and vitamin B12 levels. STUDY DESIGN: The study included 126 healthy women: 20 perimenopausal, 62 natural menopausal, and 44 surgical menopausal women. The serum levels of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglyceride, lipoprotein-a, C-reactive protein, homocysteine, folate and vitamin B12 levels were measured, and comparisons were made between the groups. RESULTS: The plasma levels of total cholesterol, triglyceride, lipoprotein-a, homocysteine and folate were non-significantly higher in natural menopause group compared to perimenopause group. Also plasma total cholesterol, lipoprotein-a, homocysteine, vitamin B12 levels were higher and high-density lipoprotein cholesterol level was lower in surgical menopause group compared to perimenopause group, the difference was not significant. The plasma level of low-density lipoprotein cholesterol was significantly higher in natural menopausal women than perimenopausal women (p<0.05). Surgical menopausal women had higher but non-significant low-density lipoprotein cholesterol levels than perimenopausal women. There was a negative correlation between age and high-density lipoprotein cholesterol in natural menopause group, and there was a positive correlation between age and homocysteine in natural and surgical menopausal groups (p<0.05). CONCLUSION: We did not find any significant difference in studied cardiovascular risk markers, folate and vitamin B12 levels in perimenopausal and postmenopausal women except low-density lipoprotein cholesterol levels.